Increased Creativity and Learning Outcomes of Class IV Students Learning IPS Through Beyond Center and Circle Time Strategy at SDN 03 Batung Bungus in Padang - Merliena Qodrio; Darnis Arief; Abna Hidayati; Budi Setiawan (Postgraduate School, Universitas Negeri Padang, 2019)
Target of this research is description of is make-up of result and kreaktivitas learn student at study of IPS use strategy of Beyond Center And Criclel Time in class of IV. this Type Research is Research of Action Class with subjek research of class student of IV counted 20 people. Research instrument the used is observation sheet of kreaktivitas student, and tes result of learning student. Pursuant to sheet analysis of kreaktivitas student in solving problem to obtain;get percentage average value at cycle of I equal to 37,5 % mounting at cycle of II become 62,5%, while student creativity in telling opinion at cycle of I obtain;get percentage average value equal to 52,5% mounting at cycle of II become 77,5%. and opinion mengemungkakan at the (time) of study process at cycle of I obtained by percentage mean 45%, mounting at cycle of II become 70%. While result learn student in understanding storey;level ( C2) at cycle of I obtain;get average value equal to 68% mounting at cycle of II become 73,75%. Inferential that strategy of Beyond Center And Criclel Time can mount result and creativity learn student at study of IPS class of IV SDN 03 Batung Bungus Kota Padang.